Inheriting the throne during the Mamluk era in Egypt in light of inscriptions on Mamluk coins - Barakat, Elshahat Anwar (Journal of Humanities & Social Sciences, 2020)
The study aimed to study the principle of inheriting the throne of the Mamluks, as inheriting the throne was one of the things that have no place in the shadow of the Mamluk state in its two parts, as the prevailing principle in governance in the Mamluk era was the principle of "authority for the one who overcame", where the one who possesses power Hegemony is the most worthy of power after the death or deposition of the existing Sultan, but the Mamluk era did not pass through periods in which the throne was inherited for some of the Sultans, as happened with the sons of Al-Zahir Baybars, and also during the era of the Bani Qalawun family, where the news and descendants inherited the throne for a period of time, But that was not a permanent matter, but rather an interim matter, until one of the princes, was able to extract power from the existing Sultan, after proving his right and strength, and this matter remained followed until the end of the Mamluks' era. This was done through the historical method based on the writings that were received on the money, and the researcher concluded:1- The inheritance of the throne existed in the Mamluk era, but for a few periods, because the Mamluks did not believe in this principle in the transfer of power.2- The Mamluk’s recognition of the principle of inheriting the throne was only part of their plan to reach the throne when their ranks were divided and one of them was above and showed his victory over other princes fighting with him.3- That some of those who inherited the rule of the Mamluks were able to prove their competence and rule for long periods, such as Khalil bin Qalawun and Al-Nasir Muhammad Yin Qalawun.4- The Mamluk doctrine never believed in the inheritance of the throne, and for you in spite of that, there were many cases of inheriting the throne in the Mamluk era. and the researcher recommended the need to rely on writings and inscriptions on the monuments to document historical events accurately.
Keywords: succession to the throne; the Mamluk state; writings; inscriptions; coins; Money